Red (SrCa)AlSiN3:Eu2+ Nitride Phosphor Particle Size of Phosphor Converted Warm White LEDs - Peng Hui Yuen; Hsien Shiung Hwang; Mutharasu Devarajan (Institute of Advanced Engineering and Science, 2014)
Red (SrCa)AlSiN3:Eu2+ nitride phosphor with different particle sizes were characterized based on physical and luminescent properties, then packaged into Chip-On-Board (COB) Warm White Light Emitting Diode (LED) modules to investigate the influence of particle size on packaging parameters and optical output of the COB LED devices. The phosphor particle sizes investigated were 10µm, 12µm and 14µm, and experimental data indicates that the emission spectrum for the red phosphor with bigger particle size is slightly red-shifted compare with the red phosphor with smaller particle size. Besides that, COB LED modules packaged with smaller red phosphor particle required slightly lesser amounts of phosphor to achieve same value of Correlated Color Temperature (CCT) range from 3500K to 3600K, while enhancing the optical output power. The average lumen output and the average efficacy of COB LED devices packaged with 10µm phosphor had an increment of 5.07% and 9.55% respectively while 12µm phosphor had an increment of 5.14% and 9.79% respectively compared to the 14µm phosphor sample.